MYTH AND MEDIA REALITY IN VIKTOR PELEVIN’S GENERATION “P”: FROM POSTMODERN DECONSTRUCTION TO METAMODERN RECONSTRUCTION (European Journal of Interdisciplinary Research and Development, 2026)
The article analyzes Viktor Pelevin’s novel Generation “P” in the context of the transition from the poetics of postmodernism to metamodernism. It examines the specific features of the author’s mythopoetics, grounded in the deconstruction of cultural codes, the simulation of reality, and intertextual play. Particular attention is paid to identifying elements of the metamodern reconstruction of myth and the search for new meaning under the conditions of a crisis of values in postmodern culture. The study focuses on the figure of the protagonist, Vavilen Tatarsky, interpreted as a bearer of the epoch’s “structure of feeling” and as a character who undergoes a transformation from postmodern simulation toward the formation of a new mythological narrative.